War, Taxes, and Borders: How Beer Created Belgium - Koen Deconinck; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
The present-day border between Belgium and the Netherlands traces back to the separation of the Low Countries after the Dutch Revolt (1566-1648) against Spanish rule. The capacity to finance war expenditures played a central role in the outcome of this conflict. Excise taxes on beer consumption were the single largest income source in Holland, the leading province of the Dutch Republic. Beer taxes thus played a crucial role in financing the Dutch Revolt which led to the separation of the Low Countries and, eventually, the creation of Belgium.
Keywords: 330